The Pedagogical Use of the Online Digital Weather Station in Teaching Mathematics to First-Year Elementary School Students - Santos, Marinalva Da Costa; Pedroso, Rogerio Santos; Cavichioli, Amanda Marques; Barni, Catia Helena Soares (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This article describes the didactic-pedagogical process of the use of the online digital weather station as a didactic-pedagogical tool in teaching mathematics to students in the 1st years A and B of elementary school at Escola Municipal Cedro Alto in the 2023 school year. The objective of this article is to socialize the effort and dedication to carry out the activities necessary to develop skills by the National Common Curricular Base, and a search to introduce Computational Thinking and Digital Culture into children's lives. The pedagogical use of the weather station demonstrated positive results, with students actively engaging in learning and developing essential skills. This experience highlighted the potential for expanding similar initiatives to enhance innovative education in other knowledge areas.